2014
DOI: 10.1121/1.4874619
|View full text |Cite
|
Sign up to set email alerts
|

The effect of language experience on perceptual normalization of Mandarin tones and non-speech pitch contours

Abstract: Context-dependent pitch perception helps listeners recognize tones produced by speakers with different fundamental frequencies (f0s). The role of language experience in tone normalization remains unclear. In this cross-language study of tone normalization, native Mandarin and English listeners were asked to recognize Mandarin Tone 1 (high-flat) and Tone 2 (mid-rising) with a preceding Mandarin sentence. To further test whether context-dependent pitch perception is speech-specific or domain-general, both langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 22 publications
2
9
2
Order By: Relevance
“…To more precisely locate the critical context duration for Mandarin tone normalization, more context durations around 250 ms should be tested, while the 1000 -and 1500-ms context durations may not be necessary in future studies. Consistent with previous studies of Mandarin tone normalization (e.g., Huang and Holt, 2009;Luo and Ashmore, 2014), this study again showed that Mandarin listeners made use of both intrinsic and extrinsic pitch cues to recognize Mandarin contour tones. The contrastive effect of context F0 on the recognition of target Tone 1-Tone 2 series was stronger in this study than in Huang and Holt (2009) and Luo and Ashmore (2014).…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…To more precisely locate the critical context duration for Mandarin tone normalization, more context durations around 250 ms should be tested, while the 1000 -and 1500-ms context durations may not be necessary in future studies. Consistent with previous studies of Mandarin tone normalization (e.g., Huang and Holt, 2009;Luo and Ashmore, 2014), this study again showed that Mandarin listeners made use of both intrinsic and extrinsic pitch cues to recognize Mandarin contour tones. The contrastive effect of context F0 on the recognition of target Tone 1-Tone 2 series was stronger in this study than in Huang and Holt (2009) and Luo and Ashmore (2014).…”
Section: Discussionsupporting
confidence: 86%
“…It is possible that the context effect on tone recognition may saturate when the context is longer than a critical duration. In Luo and Ashmore (2014), context effects on Mandarin tone recognition were actually similar for both the 500-ms non-speech contexts and 1319-ms speech contexts with the same mean F0s. Eramela (2002) tested Cantonese level tone normalization with contexts of different durations, each containing a different number of syllables with the same mid-level tone.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations